How likely does the Microenvironnmental Interaction at a Pesticide-Treated Farming Village could Potentially Affect their Community through Dermal Pathway in a Developing Country, Malaysia? - Vivien, How; Zailina Hashim; Dzolkhifli Omarin (Universiti Kebangsaan Malaysia, 2015)
Introduction This paper aims to investigate the potential pesticide dermal contamination among the agricultural community by observing the microenvironmental and macroactivity interaction between farm children and adult farmer. Methods A 24 hours timeline activity was observed and recorded in the agricultural farming village, Kuala Selangor. In this study, 2 homes were monitored for 2 days following a pesticide application. A total of 2 adult farmers and 5 children (7-10 year old) were recruited to participate in this study. Twentyfour hour videotape segments and time-activity diaries were collected during the study. Results The microenvironment and macroactivity interaction were modelled in this study. By considering only the potential dermal exposure pathway, the biological vulnerability and exposure pattern to pesticides were observed. Finding showed a greater extent of interaction between human and its environment, where adult farmers are the main contributor of environmental contaminants, and children is one of the vulnerable receivers of the contaminants’ residuals from the environment. Conclusion The daily activities and behaviors practiced by the agricultural community were among the contributing factors which help to highlight the pesticide dermal contamination pathway in the farming village. This study recommends the necessary to consider the microenvironment and macroactivity of the target community when assess their exposure levels to the environment contaminants.